Bentuk Kepemimpinan Kharismatik Guru: Belajar dari SD Islam Mu’tashim Billah Pontianak Selatan - Joni Iskandar; Imron Muttaqin (Arfannur, 2022)
Forms of Teacher Charismatic Leadership: Learning from Mu’tashim Billah Islamic Elementary School, South Pontianak. In the current leadership development, teachers must have innovation and creativity in creating ideal leadership. The rapid development of the times, especially in the field of education, must be adjusted to the ability of a person to replace the figure of a teacher. So learning with a charismatic figure is a solution for teachers in creating good learning. Charismatic leadership is all the qualities that become the authority of a person who is embedded in him so that he has bright ideas and has a good vision. One of them is the teacher’s charismatic leadership in educational institutions to contribute to creating maximum learning outcomes. This paper is at least to know about the concept of charismatic leadership, as well as the forms of charismatic leadership at SD Islam Mu’tashim Billah, South Pontianak. This study uses the field research method, which is to collect good writings from books, articles, and others that contain the theme of charismatic leadership in educational institutions. After looking at various data and information, the concept of charismatic leadership has been embedded in the human soul outwardly which needs to be explored and developed. 1. The teacher has a vision in terms of leading, 2. Has responsibility and is strong about the risks he will experience to provide the best for his school, 3. Is sensitive to his environment at school, 4. Ready to meet the needs of his students at school in providing service, 5. Have good role models, such as discipline, honesty, diligence, and showing extraordinary behavior. ABSTRAK Bentuk Kepemimpinan Kharismatik Guru: Belajar Dari Sd Islam Mu’tashim Billah Pontianak Selatan. Dalam perkembangan kepemimpinan saat ini menuntut guru harus memiliki inovasi dan kreasi dalam menciptakan kepemimpinan yang ideal. Pesatnya zaman terutama di bidang pendidikan harus lah diimbangi dengan kemampuan kepemimpinan seseorang sosok guru. Maka pembelajaran dengan sosok yang kharismatik menjadi solusi bagi guru dalam menciptkan belajar yang baik. Kepemimpinan kharismatik merupakan segala sifat yang menjadi kewibawaan seorang yang tertanam pada dirinya sehingga dia memiliki ide-ide yang cemerlang dan memiliki visi yang baik. Salah satunya adalah kharismatik guru dalam memipin di lembaga pendidikannya untuk memberikan kontribusi dalam menciptakan hasil belajar yang maksimal. Tulisan ini setidaknya untuk mengetahui tentang konsep kepemimpinan kharismatik, serta bentuk kempemimpinan kharismatik di SD Islam Mu’tashim Billah Pontianak Selatan. Penelitian ini menggunakan metode penelitian lapangan atau field research yakni mengumpulkan hasil wawancara dan dokumentasi berupa tulisan-tulisan baik berupa buku, artikel, dan lain-lain yang serempun dengan tema tentang kepemimpinan kharismatik di lembaga pendidikan. Setelah melihat berbagai data dan informasi maka konsep kepemimpinan kharismatik ini sudah tertanam dalam jiwa manusia secara lahiriah yang mana perlunya di gali dan kembangkan. 1. Guru memiliki visi dalam hal memimpin, 2. Memiliki tanggungjawab dan kuat akan resiko yang akan dialaminya untuk memberikan hal terbaik bagi sekolahnya, 3. Peka akan terhadap lingkungannya di sekolah, 4. Siap memenuhi kebutuhan-kebutuhan bagi siswa nya di sekolah dalam memberikan pelayanan, 5. Memiliki sikap teladan yang baik seperti, disiplin, jujur, rajin, serta menunjukkan siap prilaku yang luar biasa. Kata Kunci: Guru, Kepemimpinan, Kharismatik